Peran maternal self-efficacy sebagai mediator antara perceived social support dan depresi peripartum - Fitria, Ika; Permatasari, Dian Putri; Nurwanti, Ratri (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractPeripartum period is a term used to describe the period that lasts from the process of pregnancy to postpartum. Peripartum depression is associated with various negative impacts in various aspects of life, not only for mothers but also for children both short term and long term. This study aims to determine the role of maternal self-efficacy as a mediator of the correlation between perceived social support and peripartum depression using correlational quantitative methods. Study participants were taken using accidental sampling technique involving 84 women who were in the peripartum period as participants (M = 27, SD = 5.106). There are 3 research instruments used in this study, namely The Multidimensional Scale Perceived Social Support (MSPSS); Perceived Maternal Parental Self-Efficacy (PMP S-E); and Edinburgh Postnatal Depression Scale (EPDS). The results of the analysis using simple mediation analysis with the PROCESS macro from Hayes show that maternal self-efficacy mediates the relationship between perceived social support and peripartum depression. In addition, it is also known that perceived social support has a direct effect on peripartum depression.Keywords: Maternal Self Efficacy; Perceived Social Support; Peripartum Depression Abstrak Periode peripartum merupakan suatu istilah yang digunakan untuk menjelaskan periode yang berlangsung sejak proses kehamilan hingga pasca melahirkan. Depresi peripartum dikaitkan dengan berbagai dampak negatif dalam berbagai aspek kehidupan, tidak hanya bagi ibu, tetapi juga bagi anak baik jangka pendek, maupun jangka panjang. Penelitian ini bertujuan untuk mengetahui peran maternal self-efficacy sebagai mediator korelasi antara perceived social support dan depresi peripartum menggunakan metode kuantitatif korelasional. Partisipan penelitian diambil menggunakan teknik accidental sampling dengan melibatkan 84 perempuan yang berada dalam periode peripartum sebagai partisipan (M = 27, SD = 5.106). Terdapat 3 instrumen penelitian yang digunakan dalam penelitian ini, yaitu The Multidimensional Scale Perceived Social Support (MSPSS); Perceived Maternal Parental Self-Efficacy (PMP S-E); dan Edinburgh Postnatal Depression Scale (EPDS). Hasil analisis menggunakan analisis mediasi sederhana dengan makro PROCESS dari Hayes menunjukkan bahwa maternal self-efficacy memediasi hubungan antara perceived social support dan depresi peripartum. Selain itu, diketahui pula perceived social support memiliki direct effect terhadap depresi peripartum. Kata kunci: Depresi Peripartum; Maternal Self-Efficacy; Perceived Social Support